Persepsi, Motivasi, dan Kinerja Mahasiswa Akuntansi Syariah atas Pembelajaran Berbasis Kasus - Vega Wafareta; Muhammad Muhammad; Dian Syariati (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
The development of the sharia financial industry causes universities to prepare their students. The case-based learning is one way to response to the industry's need for human resources with more skills to be ready for work. Therefore, this study aims to measure the effectiveness of case-based learning as measured by the variables of perception, motivation, and performance. Based on the results of experimental tests conducted on 91 students who were divided into two classes, there were no differences in perceptions, motivations, and learning performance between case-based classes and instructional classes. This could be because case-based learning can be more effective in classes with a smaller number of students and for a longer period of time. In addition, the experience of students in receiving and analyzing previous cases is also an obstacle in the effectiveness of case-based learning. This study also found motivation to be a very important variable in increasing perceptions of skill acquisition and learning performance in case-based learning.